Joint Authorship in Scientific Publications - Tsakova, Violeta (Research Papers, 2012)
The study looks into an important, yet unstudied problem of joint scientific work – joint authorship of scientific results and its management. The main goal is to offer working rules for the creation and realization of joint authorship works; the rules are based on the nature of joint authorship, ensure fairness in the relations and protect the interests of all authors. In achieving this goal the study is aimed at disclosing the nature of joint authorship in scientific works, at determining the requirements for the arising of rights and the conditions for their management. The study looks at the regimes for arising of rights and the different types of joint authorship, the contents of commercial and non-commercial uses of joint authorship works and their corresponding rights, contracts for using joint authorship works, the rules for allocating joint authorship pay, forced coauthorship and others. The study offers solutions of existing problems that stem from joint work and collective results in science.